2021
DOI: 10.1101/2021.01.10.426131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct T cell chromatin landscapes in scleroderma subtypes

Abstract: Systemic sclerosis (SSc; scleroderma) is a poorly understood autoimmune rheumatic disease that primarily affects women. The clinical hallmark is hardening of the skin, but internal organ dysfunction is the leading cause of death. Diagnosis and treatment are complicated by heterogeneity within the disease including variable lethality, fibrosis severity, serum autoantibody production, and internal organ involvement. Important gaps remain in our knowledge of the exact molecular and cellular pathways underlying di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Our discovery of seropositivity towards multiple XIST-associating proteins in autoimmune patients introduces a novel antigen set with great clinical potential for enhancing diagnostics and disease monitoring, as autoantigens are often detected prior to or early in disease onset 61,62 . In addition to serving as effective biomarkers for disease, studies in SSc have also demonstrated the effectiveness of autoantigen analysis in patient stratification and identifying pathogenic pathways 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Our discovery of seropositivity towards multiple XIST-associating proteins in autoimmune patients introduces a novel antigen set with great clinical potential for enhancing diagnostics and disease monitoring, as autoantigens are often detected prior to or early in disease onset 61,62 . In addition to serving as effective biomarkers for disease, studies in SSc have also demonstrated the effectiveness of autoantigen analysis in patient stratification and identifying pathogenic pathways 63,64 .…”
Section: Discussionmentioning
confidence: 99%